A construção do espaço psíquico materno e seus efeitos sobre o psiquismo nascente do bebê - Aragão, Regina Orth de (2007)
This research has taken the child s therapeutic work as a starting point, passing through the therapeutic processes carried out with pregnant women, to conceive the study of the psychic processes that take place before birth. The main question of this research can be presented this way: in what manner what is anticipated and built in the mother s psyche during pregnancy will strongly influence her relation with the baby, and consequently, will present a relevant effect upon the psychic constitution of this new being. This maternal psychic preparation involves at least three dimensions: the time, the space and the identification, all of them touched by changes in the narcissistic processes of the woman. The lasting of the pregnancy establishes a time that allows the pregnant woman to pass through the process of transformation in her psyche, together with the body changes and the growing of the baby in her womb. In another dimension, these same body changes produce clear alterations in the internal feeling of her own psychic space. This psychic space changes in order to receive and to contain another being inside her body and in her life. Those processes are related to the alterations in the maternal narcissism, establishing the possibilities of one including or excluding narcissism, as we have proposed to nominate these two alternatives of maternal narcissistic position in relation to the baby. And as one fundamental intra-psychic dynamics, we can find the developments of her edipian history; mainly, the specificities of the relation between the girl and the mother of the first years of life, that will be relevant to the construction of the maternal role.